Proyecto asociativo en la parroquia Achupallas provincia del Chimborazo dedicada al faenamiento y congelamiento de cuyes para la exportación al mercado de Estados Unidos - Luna Paredes, Marcela Alejandra (2015)
Achupallas is a parish located in the province of Chimborazo, its main activity is agriculture and animal husbandry being these two livelihood but not of income for each family, the proposal developed in this paper aims at the establishment of an Association producers cuy meat for export to the US market as a means of production development for the communities that make up the parish. The organizational model defined on the basis of the People's Solidarity Economy, proposes the creation of this organization with 54 member producers to export an average of 2 tons of frozen guinea pig meat type reefer consolidated containers; export the importers held in New York dedicated to the sale of products to the Ecuadorian community and Latinos with preferences for this type of meat. Meat production involves the construction of a processing plant, which will be owned by the members and in which the participation of 8 workers in charge of the process of slaughtering, cleaning and vacuum packed meat is required; further defined as the project partners guinea pig breeders to people who have experience in this work for commercial purposes, ensuring quality in the process. The proposal shows profitable, since it generates an IRR of 52.84%, with an NPV of $ 99.935,06 making an initial investment of $ 67,290.79.